2003
DOI: 10.1038/sj.ejcn.1601569
|View full text |Cite
|
Sign up to set email alerts
|

Differences in body composition between Singapore Chinese, Beijing Chinese and Dutch children

Abstract: Objectives: To compare the relationship between body mass index (BMI) and body fat percentage (BF%) in children of different ethnic background. Design: Cross-sectional observational study. Settings: The study was performed in three different locations, Singapore, Beijing and Wageningen (The Netherlands). Subjects: In each centre 25 boys and 25 girls, aged 7 -12 y, were selected. They were matched on age, sex and body height. Methods: Body weight and body height was measured following standardized procedures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 22 publications
1
53
0
2
Order By: Relevance
“…For example, Rush and colleagues reported that for a given BMI, Maori and Pacific Island girls had lower percentage fat levels compared to European girls (27). Similarly, Deurenberg and colleagues showed that for the same BMI, Singapore children had significantly higher percentage fat levels than Beijing and Dutch children (28). This clearly illustrates that BMI is inadequate for detecting ethnic differences in LM and adiposity.…”
Section: Discussionmentioning
confidence: 89%
“…For example, Rush and colleagues reported that for a given BMI, Maori and Pacific Island girls had lower percentage fat levels compared to European girls (27). Similarly, Deurenberg and colleagues showed that for the same BMI, Singapore children had significantly higher percentage fat levels than Beijing and Dutch children (28). This clearly illustrates that BMI is inadequate for detecting ethnic differences in LM and adiposity.…”
Section: Discussionmentioning
confidence: 89%
“…Body composition is an important indicator of health status in children and adolescents (Norgan, 1990;Immink et al, 1992;Rolland-Cachera, 1995;Hills & Byrne, 1998;Malina et al, 1998;Bunc, 2001;Deurenberg et al, 2003). In the last decades, information about the relationships between body composition and physical fitness in children from developed countries has been published (Malina, 1975(Malina, , 1994Beunen et al, 1983;Malina et al, 1995Malina et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, results from a recent study of children from three different ethnic groups (Singapore Chinese, Beijing Chinese and Dutch) strongly suggest that the relationship between body fat percentage and BMI is different among children of different ethnic background. 22 If this is the case, and as Deurenberg et al 22 suggest, this observation could have implications for the relevance and use of growth charts and BMI cutoff points for different ethnic groups.…”
Section: Commentsmentioning
confidence: 99%